Quantum fields : from the Hubble to the Planck Scale - Kachelriess, Michael (Oxford graduate texts., 2018)
Michael Kachelriess introduces quantum field theory together with its most important applications to cosmology and astroparticle physics. Applications such as topological defects, phase transitions, dark matter, external gravitational fields and black holes help students to bridge the gap between undergraduate courses and research literature.